Guardians in the antiquities market: the role of specialised law enforcement units in disrupting the illicit antiquities trade - Eber, Anya (Crime and art, 2021)
This chapter examines how specialised Art, Antiquities, and Cultural Property (AACP) units, in the United Kingdom and the United States, police the illicit antiquities trade and operate as guardians within the antiquities market. The field of cultural property protection has considered several ways to disrupt the illicit antiquities trade, but more attention needs to be devoted to the role that specialised law enforcement units can play in this effort. This chapter considers how AACP units assert guardianship within the UK and the US antiquities market, and how these units increase and enhance security efforts across the antiquities trade. Drawing upon concepts from Routine Activity Theory, Nodal Governance, and Third Party Policing, this chapter examines how AACP units contribute to a networked system of guardianship in the antiquities market. This chapter argues that AACP units are an important guardianship entity within the UK and the US antiquities market, that not only assert guardianship in their own right, but also strengthen the wider guardianship network by mobilising other sectors to take on guardianship tasks and responsibilities. To examine the role that AACP units play in disrupting the illicit antiquities trade, this study collected qualitative data from law enforcement units including the United States Federal Bureau of Investigation (FBI) Art Crime Team, United States Homeland Security Investigations (HSI) Cultural Property, Art and Antiquities Program (CPAA Program), and from a sample of current and past members of the United Kingdom Metropolitan Police’s Art and Antiques Unit, as well as several other guardianship sectors across the antiquities market.